Nursing and Midwifery Students’ Perspectives of Faculty Caring Behaviours: A Phenomenological Study - Chipeta, Mep; Gombachika, Belinda; Bvumbwe, Thokozani (Bentham Open, 2022)
Aims: The study aimed at exploring faculty caring behaviours from the perspectives of university students enrolled in Nursing and Midwifery programme at one of the public universities in Malawi. Background: The concept of caring has to a larger extent been defined in the context of nursing practice and rarely in the context of nursing education. Caring for students and nurturing a caring attitude in nursing education is the first place for students to learn about the most significant values of their profession. Objective: The objective of this study was to describe faculty caring behaviours from the perspectives of university students who were studying for a degree in Nursing and Midwifery programmes at one of the public universities in Malawi. Methods: A qualitative approach utilising descriptive phenomenology as a study design was used in this study. Data was collected through semi-structured interviews at a public university in Malawi from ten (10) nursing and midwifery students who were purposively selected. All ethical considerations were followed. Data were analysed using Colaizzi’s (1978) method. Results: Five themes emerged that defined faculty caring behaviours from the student’s perspective: (1) Being available, (2) Being respectful, (3) Seeing the person in the student, (4) Being fair and (5) Communication. Conclusion Findings have shown that nursing and midwifery faculty display both caring and uncaring behaviours. The study recommends the establishment of a curriculum with caring as one of its defining philosophies; the establishment of educational faculty - student interactions based on moral and human caring principles, and advocating for faculty to embrace faculty caring to improve nursing and midwifery student's professional socialisation